Scholastic student thesaurus - Bollard, John K. (New York : Scholastic Reference, 2007)
Provides synonyms and antonyms for thousands of English words.
"Ages: 10-up"--Cover p. [4].
8.5.
5-8
Keywords: English language -- Synonyms and antonyms